Perbandingan Kejadian Anemia Pada Penggunaan Kontrasepsi Intra Uterine Device (Iud) Dan Suntik Kb 1 Bulan Di Desa Joho, Kecamatan Mojolaban, Kabupaten Sukoharjo, Jawa Tengah - Pradipta Harsatyo Kusworo (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
Anemia associated with the use of modern contraception causes changes in menstrual patterns that lead to anemia. Modern contraceptives such as sterilization, intrauterine devices (IUD), pills, birth control injections, implants, condoms, the lactation amenorrhea method (MAL) are preferred by married women in Indonesia, the prevalence was recorded at 58.7% in 2018, then 59, 7% in 2022 and the number will continue to grow until it is estimated to reach 61.9% in 2030. Contraception is an effective innovation in the public health sector, enabling family planning and pregnancy prevention, one of which is the Intra Uterine Device / IUD which is divided into four types and 1 month birth control injection which can cause side effects, one of which is anemia. The aim of the study was to analyze the comparative incidence of anemia in the use of intrauterine device (IUD) contraception and 1-month contraceptive injections in Joho Village, Mojolaban District, Sukoharjo Regency, Central Java. This study uses a comparative analysis and a pre-experimental one shot case study approach. the target population is married women or couples and the actual population is mothers using intrauterine contraception devices (IUDs) and 1 month injectable birth control. With a sample requirement of 44 respondents. There is a difference in the incidence of anemia in the use of intra uterine device (IUD) contraception and 1 month contraceptive injection in Joho Village, Mojolaban District, Sukoharjo Regency, Central Java with the average hemoglobin level of 1 month contraceptive injection users being higher than IU users